PEMBERIAN EKSTRAK REBUNG DAN PUPUK HORMON TANAMAN UNGGUL TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (Vigna radiata L) - Mardaleni Mardaleni; Selvia Sutriana (UIR Press, 2014)
The objective of this research was to know the effect of giving bamboo shot extract and superior plant hormone fertilizer on growth and yield of mung bean. The research was conducted at the experimental farm Faculty of Agriculture Riau Islamic University Pekanbaru. The research was arranged using a completely randomized design with two factorials. The first factor used bamboo shoot dosage (R) with four level treatment: without extract (R0), 1,5 ml/l water (R1), 3,5 ml/l water (R2), and 4,5 ml/l water (R3), and the second factor used superior plant hormone plant doses (H) with four level treatment: without hormone (H0), 2 cc/l water (H1), 4 cc/l water (H2), and 6 cc/l water (H3). The parameter observed consisted of pant height, flower age, harvest age, pod number per plot, pod weight per plot, and weight of 100 seeds. Data analyzed by using statistic and BNJ test at the 5% significance level. Interactionally, the application of bamboo shot extract and superior plant hormone fertilizer showed a significant effect on shoot height and number of pod per plant with the best treatment 4.5 ml/l water of shoot extract and 6 cc/l water of pant hormone. Individually, the application of bamboo shot extract affected significantly on height plant, harvest age, and weight of 100 seeds with the best dosage of 4.5 ml/l water and the application of superior plant hormone fertilizer influenced significantly on pant height, flower age, and pod weight per plant with the best dosage of 6 cc/l water.